The business style handbook [ an A-to-Z guide for effective writing on the job - Cunningham, Helen; Greene, Brendan (McGraw-Hill, 2013)
"While retaining all the valuable information that has made The Business Style Handbook a modern classic, the second edition provides new words, phrases and guidance to help you express yourself clearly, confidently and correctly on any digital platform. New to this edition: updated A-to-Z section with 250 new entries, best practices for email in a world of portable devices, insights from communications executives at global companies.